Small state, smart influence: China’s Belt and Road extended to New Zealand - Lin, Jake (Henry Stewart Talks, 2019)
Belt and road initiative (BRI), New Zealand, China, Export, Asian infrastructure investment bank (AIIB), Institutional agenda-setting power, Soft power, Normative power, Smart influence